Numerical investigation of impingement heat transfer on the crossflow channel with vortex generators. (25th January 2022) - Yang, Yue; Mao, JuiKui; Chen, Pingting; Wang, Feilong; Tu, Zecan
Highlights: A new vortex generator with downstream common-flow-down configuration is obtained. The counter rotating vortex pair is extruded by a recirculation behind the jet. The maximum enhancement of area averaged Nusselt number can reach up to 69.7%. The additional increase of friction coefficient is lower than 10%. Abstract: Vortex generators (VGs), as novel measures for suppressing a crossflow, have been used for the promotion of jet impingement heat transfer. In this study, to explore more VGs' benefits, numerical simulations are investigated for the comparisons of a jet in crossflow with four VGs, considering the heat transfer performances and the flow interaction mechanisms. VGs with common-flow-up or common-flow-down configurations are arranged in the upstream or downstream of the jet hole. Parameter studies are carried out by varying the crossflow-to-jet ratio from 0.19 to 0.32, VG heights from 1/8 H to 1/2 H ( H is the jet-to-wall distance), and spacings between the jet and the VGs from 0 d to 2 d ( d is the jet hole diameter). Results show that a new VGs with downstream common-flow-down configuration (DCFD) is obtained with favorable enhancement of heat transfer, which is competitive to the upstream common-flow-up configuration (UCFU) studied in previous work. With the DCFD configuration, the extrusion of the counter rotating vortex pair is caused by a recirculation region generated behind the jet, which gives more blockage to the crossflow. In addition, the heat transfer for the DCFD case is promoted with the increasing height of the VGs, and decreasing the spacing between the VGs and the jet. The maximum enhancement in area averaged Nusselt number for DCFD case can reach up to 69.7% with a small increase in the friction coefficient of lower than 10%. This study will present much more possibilities for the heat transfer enhancement in more complex system, such as jet array system and nonuniform crossflow system.